Inflation in macroeconomic terms - Nina Dubiel; Jakub Łomozik (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The modern economy, which dynamically responds to both internal and global changes, is exposed to fluctuations in the level of inflation, which have a significant impact on monetary policy, the stability of financial markets and consumer behavior. Understanding this phenomenon and the ability to analyze its effects are therefore becoming indispensable not only for economists, but also for every citizen operating in the realities of a market economy.